2006
DOI: 10.5070/v422110133
|View full text |Cite
|
Sign up to set email alerts
|

Novel Visual Lures for the Management of Brushtail Possums

Abstract: The successful management of vertebrate wildlife populations can be dependent on the availability of reliable monitoring methods, and, depending on the status of the species in question, effective methods of conservation or control. The brushtail possum, introduced to New Zealand from Australia, is considered New Zealand's number one vertebrate pest. We assessed possum preferences for 3 types of visual lures and the potential use of this information for enhancing existing possum control technologies. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…There have been a number of techniques explored for luring possums to a bait station, including smell, taste, sound, and visual stimuli (Ogilvie and Sakata 2006, Warburton and Yockney 2009, Thomas and Maddigan 2004. Possums seem to be attracted to light; studies have shown that fluorescent lures beside wax bait interference devices will give higher number of bites than those without a fluorescent lure .…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of techniques explored for luring possums to a bait station, including smell, taste, sound, and visual stimuli (Ogilvie and Sakata 2006, Warburton and Yockney 2009, Thomas and Maddigan 2004. Possums seem to be attracted to light; studies have shown that fluorescent lures beside wax bait interference devices will give higher number of bites than those without a fluorescent lure .…”
Section: Discussionmentioning
confidence: 99%
“…Visual lures have been used to attract brushtail possums ( Trichosurus vulpecula ) in New Zealand where they are a pest species, for management practices. These visual attractants were more effective when they included a luminescent strip as opposed to plain or UV reflective strips (Short, Turner & Risbey, ; Ogilvie et al ., ). Decoys are widely used as attractants for hunting, strongly suggesting wider applicability in conservation efforts for any colonial or aggregating species.…”
Section: Use and Effectiveness Of Sensory Modes In Conservationmentioning
confidence: 97%
“…Research on possums has considered biological controls (Cross et al, 2011) and both visual (Ogilvie et al, 2006) and auditory lures (Kavermann et al, 2012). Live rats as intraspecies lures have been investigated as have interspecies olfactory attractants such as insect pheromones (Gould et al, 2007).…”
Section: Introductionmentioning
confidence: 99%